A narrative review of evidence to support increased domestic resource mobilization for family planning in Nigeria - Chinyere Ojiugo Mbachu; Ifunanya Clara Agu; Chinazom N. Ekwueme; Anne Ndu; Obinna Onwujekwe (BMC, 2023)
Abstract Background Family planning (FP) is an important public health intervention that is proven to reduce unplanned pregnancies, unsafe abortions, and maternal mortality. Increasing investments in FP would ensure stability and better maternal health outcomes in Nigeria. However, evidence is needed to make a case for more domestic investment in family planning in Nigeria. We undertook a literature review to highlight the unmet needs for family planning and the situation of its funding landscape in Nigeria. A total of 30 documents were reviewed, including research papers, reports of national surveys, programme reports, and academic/research blogs. The search for documents was performed on Google Scholar and organizational websites using predetermined keywords. Data were objectively extracted using a uniform template. Descriptive analysis was performed for quantitative data, and qualitative data were summarized using narratives. Frequencies, proportions, line graphs and illustrative chart were used to present the quantitative data. Although total fertility rate declined over time from 6.0 children per woman in 1990 to 5.3 in 2018, the gap between wanted fertility and actual fertility increased from 0.2 in 1990 to 0.5 in 2018. This is because wanted fertility rate decreased from 5.8 children per woman in 1990 to 4.8 per woman in 2018. Similarly, modern contraceptive prevalence rate (mCPR) decreased by 0.6% from 2013 to 2018, and unmet need for family planning increased by 2.5% in the same period. Funding for family planning services in Nigeria comes from both external and internal sources in the form of cash or commodities. The nature of external assistance for family planning services depends on the preferences of funders, although there are some similarities across funders. Irrespective of the type of funder and the length of funding, donations/funds are renewed on annual basis. Procurement of commodities receives most attention for funding whereas, commodities distribution which is critical for service delivery receives poor attention. Conclusion Nigeria has made slow progress in achieving its family planning targets. The heavy reliance on external donors makes funding for family planning services to be unpredictable and imbalanced. Hence, the need for more domestic resource mobilization through government funding.